The yeast halotolerance determinant Hal3p is an inhibitory subunit of the Ppz1p Ser/Thr protein phosphatase - de Nadal, Eulàlia (The National Academy of Sciences, 1998)
Components of cellular stress responses can be identified by correlating changes in stress tolerance with gain or loss of function of defined genes. Previous work has shown that yeast cells deficient in Ppz1 protein phosphatase or overexpressing Hal3p, a novel regulatory protein of unknown function, exhibit increased resistance to sodium and lithium, whereas cells lacking Hal3p display increased sensitivity. These effects are largely a result of changes in expression of ENA1, encoding the major cation extrusion pump of yeast cells. Disruption or overexpression of HAL3 (also known as SIS2) has no effect on salt tolerance in the absence of PPZ1, suggesting that Hal3p might function upstream of Ppz1p in a novel signal transduction pathway. Hal3p is recovered from crude yeast homogenates by using immobilized, bacterially expressed Ppz1p fused to glutathione S-transferase, and it also copurifies with affinity-purified glutathione S-transferase-Ppz1p from yeast extracts. In both cases, the interaction is stronger when only the carboxyl-terminal catalytic phosphatase domain of Ppz1p is expressed. In vitro experiments reveal that the protein phosphatase activity of Ppz1p is inhibited by Hal3p. Overexpression of Hal3p suppresses the reduced growth rate because of the overexpression of Ppz1p and aggravates the lytic phenotype of a slt2/mpk1 mitogen-activated protein kinase mutant (thus mimicking the deletion of PPZ1). Therefore, Hal3p might modulate diverse physiological functions of the Ppz1 phosphatase, such as salt stress tolerance and cell cycle progression, by acting as a inhibitory subunit.